Efficacy and safety of intravitreal aflibercept injection in wet age-related macular degeneration: outcomes in the Japanese subgroup of the VIEW 2 study. Issue 1 (8th August 2014) - Ogura, Yuichiro; Terasaki, Hiroko; Gomi, Fumi; Yuzawa, Mitsuko; Iida, Tomohiro; Honda, Miki; Nishijo, Koichi; Sowade, Olaf; Komori, Tetsushi; Schmidt-Erfurth, Ursula; Simader, Christian; Chong, Victor
Abstract : Background/aims: To evaluate efficacy and safety of intravitreal aflibercept (IVT-AFL) in Japanese patients with wet age-related macular degeneration (wAMD) from the VIEW 2 trial. Methods: In this double-masked study, patients were randomised to: 0.5 mg IVT-AFL every 4 weeks (0.5q4); 2 mg IVT-AFL every 4 weeks (2q4); 2 mg IVT-AFL every 8 weeks (2q8) after 3 monthly injections; or 0.5 mg ranibizumab every 4 weeks (Rq4). Main efficacy outcomes included vision maintenance and best-corrected visual acuity (BCVA) at week 52. Results: At week 52, all Japanese patients in the IVT-AFL groups (n=70) maintained vision, compared with 96% of Japanese patients (n=23/24) treated with ranibizumab. Japanese patients in all treatment groups showed improvement in BCVA after treatment. The Rq4, 2q4 and 2q8 groups experienced similar gains in BCVA from baseline. The 0.5q4 group had higher gains due to an unexpected drop in BCVA between screening and baseline. Central retinal thickness and mean area of choroidal neovascularisation decreased in all treatment groups with similar magnitude. Ocular treatment-emergent adverse events were balanced across treatment groups. Conclusions: IVT-AFL was effective and well tolerated in Japanese patients. Outcomes in this population were consistent with those in the overall VIEW 2 population. Trial registration number: NCT00637377.